Strengthening Auditing and Accounting Performance in Sub-Saharan Africa : The Education and Training Factors - Johnson, Sonia R. (World Bank, Washington, DC, 2012)
This study provides an overview of the accounting profession and the education and training of accountants in Sub-Saharan Anglophone Africa. It looks at: the profession; accounting examinations; accounting degrees; the education of accountants and accounting technicians; the training of accountants and accounting technicians; and continuing professional education (CPE). This study provides an overview of the accounting profession and the education and training of accountants in Sub-Saharan Anglophone Africa. The study found that there were good and poor examples of accounting education in Anglophone Africa. On the good side are colleges like the Zambia Centre for Accountancy Studies (ZCAS) and the Strathmore College in Kenya, which are providing quality accounting education. In contrast, Uganda fares somewhat poorly. It has only just established an accounting body, it has no national examinations, and the accounting training institutions are struggling to prepare students for overseas examinations. External support for accounting education in Anglophone Africa has been reasonably successful, with donor-funded colleges such as ZCAS obtaining pass rates almost twice the worldwide average. Assistance however, is still required to help the profession develop.